METHOD DEVELOPMENT AND VALIDATION OF RUPATADINE FUMARATE IN BULK BY UV SPECTROSCOPY - Anusha Gandi; N.V.N.Koteswara Rao; G.Anusha; G.Preethi; D.Mounika (International Journal of Ayurveda and Pharma Research, 2020)
A simple, rapid, precise and economical spectrophotometric method has been developed for quantitative analysis of rupatadine fumarate in bulk form. The objective of the present work is to develop and validate stability indicating simple and accurate method for the determination of Rupatidine fumarate using accurate UV spectroscopic method. The solutions of standard were prepared in methanol. Based on the solubility and physical parameters of the drug the standard stock solution of the drug was prepared and wavelength maxima were determined. The ?max was found to be 232nm. Based on the absorbance maxima of the drug dilutions were prepared and in the formulation estimated was carried out. The method can be adopted in routine analysis of Rupatadine fumarate in bulk form and it involves relatively low cost solvents and no complex extraction techniques. The drug showed linearity in the range of 2-10µg/ml with a correlation co-efficient of 0.999. The ruggedness was found to be 0.28 The detection limit and quantification limit of the method were calculated as the 0.4714µg/ml and 1.5557µg/ml. The method validated for different validation parameters such as linearity, accuracy, precision, detection limit, quantization limits, robustness, ruggedness and the results were found to be within the acceptance limits as per the guidelines of International Conference on Harmonisation (ICH).